Editorial: XI Peruvian Congress of Obstetrics and Gynecology; VII Bolivarian Day of Gynecology and Obstetrics - Huamán, José (2015)
There is no greater than seeing a dream realized plasma despite the difficult times that we lived satisfaction. The XI Bolivarian Congress of Gynecology and Obstetrics and the Bolivarian DAY VII of Obstetrics and Gynecology took place on 3 and October 7, 1993, opening for an event of such proportions the halls of the National Museum. The significance of the Congress is expressed in the figures of 1175 participants, 23 foreign teachers and 215 national teachers who presented and discussed the most innovative and varied topics of expertise.